Numerical investigation of the influence of mineral mesostructure on quasi-static compressive behaviors of granite using a breakable grain-based model - Pan, Cheng; Zhao, Guangming; Meng, Xiangrui; Dong, Chunliang; Gao, Pengfei (Frontiers in Ecology and Evolution, 2023)
The mesostructure of brittle rocks plays a crucial role in determining their mechanical properties and failure mode. To comprehensively investigate the influence of rock mesostructure (e.g., grain size distribution, grain shape, and average grain size) on the mechanical behavior of granite, a breakable polygonal discrete element model is developed. This model incorporates mineralogical composition, grain size distributions, and grain shape, providing a more realistic representation of rock mesostructure. Using this model, numerical specimens with different mesostructures were created to represent variations in grain size, shape, and distribution. A series of quasi-static uniaxial compressive loading tests were conducted on these specimens to examine their peak strength and macroscopic failure modes. The findings indicate a strong linear relationship between the quasi-static compressive strength of the rock and mesostructure parameters, including the average grain size, grain size coefficient, and grain roundness. Furthermore, the simulation results demonstrate that the rock mesostructure significantly impacts the quasi-static compression failure mode. The proposed breakable polygonal discrete element model has the potential to predict the macroscopic behavior of brittle rocks, providing a reliable method to study the effect of mesostructure on the quasi-static compressive mechanical behavior of rocks.